A study on personal protective equipment use among health care providers, Tamil Nadu - P. A., Archana Lakshmi; Jennifer H., Gladius; Stanly A., Meriton; Paul, Christina Mary (International Journal Of Community Medicine And Public Health, 2018)
Background: Personal protective equipment (PPE) limits the health care workers contact with all secretions or biological products. This study was planned to find gaps between use of PPE among the health care providers (HCPs). The objective of the study was to evaluate appropriate use of PPE among health care providers in tertiary centres Tamil Nadu. Methods: A cross sectional study was done during November 2014 to October 2015 in two tertiary health care institutions. All health care providers (Doctors, nurses and technicians) who had more than one year experience and gave informed consent were included. Data collected by pretested structured questionnaire. Data analysis was done using SPSS 20v and summarized by descriptive statistics. Proportion and Chi-square was calculated at 5% α. Results: HCPs included in the study were 1060. Among them, there were 412(38.9%) doctors, 550 (51.9%) nurses and 98 (9.2%) technicians. Among 862 HCPs who work outside the operation theatre (OT) and ICU, appropriate uses of PPE were only 156 (18.1%). It was high among doctors 109 (31.5%) followed by nurses 39 (9.3%) and technicians 8 (8.2%) which was statistically significant p=0.0001. HCPs working in OT and ICU were 423 and 183 respectively. Among HCPs working in OT, appropriate use of gloves, mask, apron, gown and hair cover was 100%. But the use of goggles and shoe cover was very low. The reasons for inappropriate use of PPE was non availability 562 (78%) followed by not aware of the importance 77 (11%). Conclusions: The study showed inappropriate use and lack of adequate knowledge on infection control practices emphasizing that periodic re-training is needed.